Needs Analysis of Science and Technology Teachers towards Alternative Assessment Methods - Mutlu, Neşet; Özden, M. Yaşar (My University, 2017)
The purpose of this study is to find out science and technology teachers’ perceptions about their knowledge about constructivist approach and alternative assessment and evaluation, technology use in education and their preferences about delivery of in-service trainings. 21 science and technology teachers were selected purposefully in this study. To understand their perceptions, semi-structured interviews as a qualitative method were used (Merriam, 1998). Study findings showed that both experienced and inexperienced teachers had troubles in preparation and application of alternative assessment methods. Moreover, study revealed that science and technology teachers are familiar with computers and internet applications. Lastly, science and technology teachers emphasized advantages of online training over face-to-face training such as accessibility, flexibility, and being up-to-date. There was no expression about disadvantages of online training. Most of the participants giving feedback about faceto-face training marked disadvantages of it as incompetent trainers, shallow content and lectures without practice. It is concluded that teachers needs trainings about alternative assessment and evaluation methods and they see the online in-service training method be more beneficial compared to face-to-face training method.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği; Eğitim; Eğitim Araştırmaları; Bilgi; Belge Yönetimi